The Analyzing The Accounting Information System Sales Cash In Improve The Efectivity Sales - Mauliyah, Nur Ika (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2020)
The aims of this research are: Analyzing the Accounting System of cash sales implemented at UD. Tani Mulyo with Accounting System whether it is appropriate theory. This research is a case study (1) Describing the cash sales activities and describing functions, procedures, documents, accounting records for cash sales, (2) Provide comparisons to Accounting Information System applied to SIA according to the theory adapted (3) Create Flowchart in accordance with existing procedures. Based on the analysis it could be concluded that: (1) The existence of overlapping tasks and responsibilities in the work on related functions. (2) The absence of Accounting Information System and Flowchart. (3) Document usage and accounting records in the accounting system is still simple and manual. (4) Although the sales are done smoothly, but in accordance with the system and procedures appropriate for use in the company will further improve the effectiveness of the sales activities. With the increase in sales effectiveness, the company's results are also increasing.